BIOCHEMICAL PROPERTIES OF MICROSCOPIC FUNGI CULTURES ISOLATED FROM INJURED KEROID FORMATIONS OF SKIN - Kulynych, S.M.; Kabluchka, A.P.; Petrenko, M.O.; Kravchenko, S.O.; Kanivets, N.S. (World of Medicine and Biology, 2018)
From 2007 to 2016, 3694 animals were studied in nine farms of the Poltava and Kirovograd regions, including 3307 cows, 300 sheep and 87 horses. The total of 112 samples of the injured hoof horn taken from 83 animals were subject to mycological examination: 63 cows aged 3-5 years, 10 horses aged 5-9, and 10 sheep 4-7 years old. The sick animals were divided into groups according to their species affiliation. According to research results, 20 fungi species of 14 genera were allocated. From the microscopic fungi isolated from the destroyed keratinized horny capsule structures the highest keratinase, hemolytic phospholipase and lecithinase activity was found in S. brevicaulis fungus species (p
Keywords: microscopic fungi; keratinolytic; lecithinase; phospholipase and hemolytic activity